Co-occurrence of hypertension and type 2 diabetes: prevalence and associated factors among Haramaya University employees in Eastern Ethiopia - Motuma, Aboma; Gobena, Tesfaye; Roba, Kedir Teji; Berhane, Yemane; Worku, Alemayehu; Regassa, Lemma Demissie; Tolera, Abebe (Frontiers in Public Health, 2023)
Abstract Background: Both Hypertension and diabetes mellitus are public health concerns in low-and middle-income countries. In Ethiopia, there is limited evidence on the co-occurrence of hypertension and type 2 diabetes (T2DM). This study was conducted to assess the co-occurrence of hypertension and T2DM and its associated factors among Haramaya University employees in Eastern Ethiopia. Methods: A cross-sectional survey was conducted among 1200 employees at Haramaya University by using a simple random sampling technique from December 2018 to February 2019. Blood pressure was measured by using a digital measuring device on the non-dominant hand after resting for at least 10 minutes. Blood glucose and lipid profile measurements were done by collecting 6 ml of venous blood samples after 8 hours of overnight fasting. Data were analyzed using Stata 16 software. Hypertension was defined as systolic blood pressure ≥140mmHg and or diastolic blood pressure ≥90 mmHg, while diabetes was defined as fasting blood glucose ≥ 126mg/dl. Descriptive and logistic regression analyses were conducted (AOR) with 95% confidence interval (CI) and statistical significance was declared at p-value < 0.05. Results: The prevalence of hypertension and T2DM were 27.3% and 7.4% respectively. The co-occurrence of hypertension and T2DM was 3.8 %. The prevalence of HTN and T2DM co-occurrence was higher with older age (AOR=3.97; 95 % CI:1.80-8.74), higher level of education (AOR=0.39; 95% CI:0.17-0.89), Khat chewing (AOR=2.76; 95 % CI: 1.23-6.18), body mass index ≥ 25 kg/m2 (AOR=5.11; 95 % CI: 2.06-12.66), sedentary behavior ≥8 hours per day (AOR=6.44; 95 % CI: 2.89-14.34). A Higher frequency of consuming fruits and vegetables was associated with a lower prevalence of HTN and T2DM co-occurrence (AOR=0.10; 95 % CI: 0.04-0.22). Conclusions: Co-occurrence of hypertension and T2DM was substantially prevalent among Haramaya University employees. Advanced age, khat consumption, a higher level of education, being overweight, and sedentary life were associated with the increased prevalence of co-occurrence while consuming more fruits and vegetables decreased the co-occurrence. Minimizing Khat chewing, improving fruit and vegetable consumption, and regular exercise with screening for older employees may tackle the alarming increase and impact of hypertension and T2DM in university employees in eastern Ethiopia.